Academic supervision and work motivation as a contributing factor of teacher competence - Azwardi, Azwardi (Indonesian Educational Administration and Leadership Journal (IDEAL), 2019)
This study aims to find an empirical contribution of academic supervision by school supervisors and work motivation to teacher competence. This research is a quantitative study with survey design, a cross-sectional technique. Samples were 84 respondents. Data were collected through a questionnaire and analyzed using descriptive analysis techniques, as well as regression analysis through SPSS. The findings of this study indicate that supervision by supervisors includes high categories. The R2 value of the contribution of academic supervision of school supervisors to competencies was 30.4%. Contribution of teacher's work motivation to teacher competency R2 value was 46.1%. The contribution of academic supervision of school supervisors and work motivation, to teacher competence, was 47%. Recommendations for the betterment of education in Indonesia are offered.